Biological control: Pomacea haustrum Reeve, 1856 (Mollusca pilidae) over planorbids under laboratory conditions - Guimarães, Carlos Tito (Revista de Saúde Pública, 1983)
The biological control of planorbids (Biomphalaria straminea Dunker, 1848; B. tenagophila Orbigny, 1835 and B. glabrata Say, 1818) through the predation of their eggmasses by the pilid Pomacea haustrum Reeve, 1856, was observed under laboratory conditions. Of 829 eggmasses laid by B. straminea, 203 (24.5%) were exposed to 10 specimens of P. haustrum and 200 (98.3%) of them were predation. Of 892 eggmasses laid by B. tenagophila, 210 (22.5%) were exposed to 10 specimens of P. haustrum and 194 (97.0%) were predate. Of 1,300 eggamsses laid by B. glabrata, 657 (50.5%) were exposed to 10 specimens of P. haustrum and were totally predate. Parallel to this the possible interaction of pomaceas and planorbids when they lived in the same aquarium has been observed.